(untitled) (Journal of Bio-Science, 2015)
Context: Phytoplanktonic community structure in an aquatic body embodies the energy transfer through this phase and indicates the tropic status. Objectives: The present study was conducted to assess the phytoplankton abundance and species composition of Mouri River, Khulna, Bangladesh. Materials and Methods: Water samples were collected from six different stations once in a week for a period of 6 months (February- July) 2010. Results: In total 48 different species of 23 genus and 4 families were identified. Phytoplankton abundance varied from 805 to 1788 individuals/L in different stations. The highest abundance was observed for the family chlorophyceae that constituted 27-50.56% of the total phytoplankton biomass throughout the river. Highest number of phytoplankton species (22) was also recorded for the family chlorophyceae. The most diverse genus was Navicula (6). Some aspects of the water quality parameters were measured by regression analysis and significant correlations were also observed between water quality parameters and phytoplankton abundance. Water temperature, pH, DO, Free CO2, alkalinity, hardness, calcium and magnesium showed positive correlations with total phytoplankton abundance where as transparency, TDS, TSS, sulfate phosphate and nitrite showed negative correlations. Conclusion: In most of the cases, phytoplankton abundance and water quality parameters showed greater deviation from the optimum level. However, the results of the present experiment confirmed the polluted water of the river. DOI: http://dx.doi.org/10.3329/jbs.v21i0.22516 J. bio-sci. 21: 27-34, 2013